Sistem Panel Pompa Hydrant Menggunakan Rangkaian Star-Delta di PT.Tiga Kreasi Indonesia - Muhammad Reza Nugraha; Mustofa Abi Hamid (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Carrying out work practices in this industry is one of the requirements for the industrial practice course. This practical activity aims to find out directly the state of the industry in terms of work readiness. The aim of this industrial practice activity focuses on finding out what components are contained in the Star-Delta hydrant pump panel, knowing the process of installing the Star-Delta hydrant pump panel and knowing how the Star-Delta panel works. In implementing this industrial practice, observation methods, library observations and interviews are used. PT. Tiga Kreasi Indonesia is a company that operates in the field of manufacturing electrical panels, with one of its products being Star-Delta hydrant pump panels to stabilize air pressure in hydrant pump lines. The hydrant pump's star delta panel functions to control and secure what happens if undesirable things happen, such as protecting a building or factory. This research produces new knowledge and understanding regarding the design of Star-Delta Panel hydrant pumps which are widely used in homes, factories and offices to minimize the occurrence of fires.